The influence of geographic heterogeneity in predation pressure on sexual signal divergence in an Amazonian frog species complex - Trillo, PA (2013)
We thank R. Page, M. S. Caldwell and P. Jones for many thoughtful comments on the manuscript. We thank R. Taylor for loaning frog models, staff at La Selva Lodge and the Yasuni Research Station for logistical support and Manuel Mejia and Andrea Narvaez for help with fieldwork. We also thank J. Cordova, the Museum of Natural History at UMSM, Peru and QCAZ at Pontifica Universidad Catolica del Ecuador for logistic help and advice. This research was funded by a National Geographic Society-Waitt grant, Colorado State University to CF, a National Science Foundation IOS-0940466 grant to KH and a UNESCO-L'Oreal-CONCYTEC fellowship to PAT. The research was approved by the Institutional Animal Care and Use Committee at Colorado State University (09-027A-01). The work was facilitated by ongoing collaborations with the Yanayacu Natural History Research Group.